Information Extraction From Malay Vehicle Advertisement Text Using Natural Language Processing Techniques. - Norfadila, Mahrom (2007)
Some of the vehicle advertisements are represented in textual documents, and it requires a reader to read the entire document and understands its content before the important information can be extracted. This process consumes more time instead of having a system that can extract the important information from the document automatically without the reader needs to read the whole document. In this study, a prototype system was developed to assist a reader to extract important information from the Malay vehicle advertisement by applying natural language processing (NLP) techniques. The NLP techniques that have been used are focused on the syntactic processing.